Colour image encryption using an improved version of stream cipher and chaos. (21st July 2022) - Deb, Subhrajyoti; Bhuyan, Bubu; Kar, Nirmalya; Reddy, K. Sudheer
This paper proposes a novel image cryptosystem based on chaos theory and a modified version of Grain-128 cipher. Pixel and bit-level permutation of the plain image is performed by Hilbert curve and Hénon map to disrupt high correlation. The wellknown Grain-128 cipher is modified by replacing its Boolean function and reducing its state size. Output of modified Grain-128 cipher is bitwise XORed with randomised image data to produce cipher image. The modifications in the Grain-128 cipher is done in order to achieve higher encryption decryption efficiency. However, the proposed nonlinear function of the cipher shows superior performance compared to nonlinear functions used in several cryptographic algorithms in terms of nonlinearity value. Experimental result from statistical tests and efficiency analysis confirms the superiority of the proposed cryptosystem.